PENGEMBANGAN MEDIA LAGU MATEMATIKA DALAM PEMBELAJARAN DI KELAS V SEKOLAH DASAR - Untari, Mei Fita Asri; Cahyadi, Fajar; Budiningtyas, Ade Kalpila (Universitas Pendidikan Indonesia, 2017)
Mathematics is considered a difficult material with various formulas that is not only memorized but also need to be understood. This makes the mathematics learning outcomes in primary schools is low. To overcome these problems, there should be a learning innovation to facilitate learners in the study of mathematical formulas. One type of media is media of math song about math formula to help students in solving mathematical problems. Media of song about mathematical formula is expected by learners, teachers, and parents to make it easier to understand the material. This was reinforced by the results of limited testing in class V, they are media of mathematical formula songs is accepted by learners and teachers having the advantage of growing enthusiasm of the participants thus they are more eager, more focus and more active to take part in the mathematics learning.Keywords: development, songs media, elementary school mathematics.